Managing people in sport organizations : a strategic human resource management perspective - Taylor, Tracy; Doherty, Alison; McGraw, Peter; ScienceDirect eBooks (Oxford, UK ; Boston : Butterworth-Heinemann, 2008)
Managing People in Sport Organizations provides a comprehensive overview of the theory and practice of managing people within a human resource management framework. It provides the reader with the skills to understand and work with people in sport organizations and, given the significant changes in sport organizations over the past twenty years, it addresses the issues of managing organizational complexity and how human resources adds value. Written by a team of expert authors it: * Provides a systematic approach to managing people based on well established conceptual frameworks supported by substantial empirical research * Analysis and explains how to understand and work with people in organisationally complex situations * Outlines how HR can support organisational strategy, positively impact performance and deliver sustainable success * Designs a strategic human resource management plan that is effective, sustainable and able to adapt to changing conditions. * Covers the key research findings in the key area of HR in sport. With each chapter including learning objectives, key issues, international cases studies and supported by online PowerPoint slides Managing People in Sport Organizations is the definitive text for this crucial area of sports management. * Provides a comprehensive and systematic approach to the theory and practice of managing people in sports organisations * Analyses and explains how to understand and work with people in organisationally complex situations * Outlines how HR can support organisational strategy, positively impact performance and deliver sustainable success.
8. Motivation and rewards management in sport organizations -- 9. Sport organizations and employee relations -- 10. Succession and talent management -- 11. Sport organizations and diversity management -- 12. Evaluating and improving human resource management -- 13. Managing change and future challenges in sport organizations.
Includes bibliographical references (pages 281-296) and index.
Print version record.
Elsevier
Keywords: Sports administration; Personnel management; Associations, institutions, etc. -- Management; Personnel -- Direction; Sports -- Gestion; Associations -- Gestion; SPORTS & RECREATION -- Essays; SPORTS & RECREATION -- History; SPORTS & RECREATION -- Business Aspects; SPORTS & RECREATION -- Reference; GAMES -- Gambling -- Sports; TRAVEL -- Special Interest -- Sports; Associations, institutions, etc. -- Management; Personnel management; Sports administration; Sport; Management; Electronic books